Sequential Evolution and Escape from Neutralization of Simian Immunodeficiency Virus SIVsmE660 Clones in Rhesus Macaques - Wu, Fan (American Society for Microbiology, 2012)
Simian immunodeficiency virus (SIV) infection of rhesus macaques has become an important surrogate model for evaluating HIV vaccine strategies. The extreme resistance to neutralizing antibody (NAb) of many commonly used strains, such as SIVmac251/239 and SIVsmE543-3, limits their potential relevance for evaluating the role of NAb in vaccine protection. In contrast, SIVsmE660 is an uncloned virus that appears to be more sensitive to neutralizing antibody. To evaluate the role of NAb in this model, we generated full-length neutralization-sensitive molecular clones of SIVsmE660 and evaluated two of these by intravenous inoculation of rhesus macaques. All animals became infected and maintained persistent viremia that was accompanied by a decline in memory CD4(+) T cells in blood and bronchoalveolar lavage fluid. High titers of autologous NAb developed by 4 weeks postinoculation but were not associated with control of viremia, and neutralization escape variants were detected concurrently with the generation of NAb. Neutralization escape was associated with substitutions and insertion/deletion polymorphisms in the V1 and V4 domains of envelope. Analysis of representative variants revealed that escape variants also induced NAbs within a few weeks of their appearance in plasma, in a pattern that is reminiscent of the escape of human immunodeficiency virus type 1 (HIV-1) isolates in humans. Although early variants maintained a neutralization-sensitive phenotype, viruses obtained later in infection were significantly less sensitive to neutralization than the parental viruses. These results indicate that NAbs exert selective pressure that drives the evolution of the SIV envelope and that this model will be useful for evaluating the role of NAb in vaccine-mediated protection.